Polyvinyl alcohol-borate hydrogel containing magnetic adsorbent for surface decontamination. (November 2017) - Yang, Hee-Man; Hwang, Kyu Sun; Park, Chan Woo; Lee, Kune-Woo
Highlights: Temperature-sensitive and strippable surface decontaminant were developed. It is composed of magnetic Cs adsorbent and PVA-borate hydrogel effectively removed 137 Cs from the contaminated surface. PVA-borate hydrogel can be reused via magnetic separation of adsorbent in used film. A new eco-friendly volume-reduction method for radioactive waste was suggested. Abstract: A stimuli-sensitive, strippable coating material that consisted of a magnetic field-sensitive adsorbent with excellent 137 Cs adsorption and a temperature-sensitive, elastic Poly vinyl alcohol (PVA)-borate hydrogel was developed for the decontamination of 137 Cs-contaminated surfaces. The viscous solution of adsorbent/PVA-borate complex can easily be applied to a surface at 50 °C, subsequently forming an adsorbent/PVA-borate hydrogel film that is strippable from the surface at room temperature. The film displayed a good removal efficiency of 83.46% and the decontamination factor (DF) of 6.05 from the 137 Cs-contaminated surface due to the presence of the adsorbent, which had a large distribution coefficient for Cs (3.34 × 10 4 mL/g). Moreover, the PVA-borate complex can be reused following a simple addition of water via the magnetic separation of the adsorbent, which can capture 99.071% of the 137 Cs in the used hydrogel film. These findings suggest a new eco-friendly volume-reduction method for radioactive waste after surface decontamination.